2012
DOI: 10.1063/1.4737412
|View full text |Cite
|
Sign up to set email alerts
|

Complementary metal–oxide–semiconductor compatible high efficiency subwavelength grating couplers for silicon integrated photonics

Abstract: We demonstrate a through-etched grating coupler based on subwavelength nanostructure. The grating consists of arrays of 80 nm  343 nm rectangular air holes, which can be patterned in a single lithography/etch. A peak coupling efficiency of 59% at 1551.6 nm and a 3 dB bandwidth of 60 nm are achieved utilizing the silicon-on-insulator platform with a 1 lm thick buried-oxide layer for transverse electric mode. The performance is comparable to gratings requiring much more complicated fabrication processes. V

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
82
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 120 publications
(84 citation statements)
references
References 24 publications
2
82
0
Order By: Relevance
“…In addition, the highest CE of only −0.58 dB with 3 dB bandwidth of 71 nm was obtained at a coupling angle of 13°. The back reflection of the grating coupler was extracted from the contrast of the Fabry-Perot (FP) fringes of the fiber-to-fiber transmission spectrum, and is lower than 1.4% at the peak coupling wavelength, which is comparable to previous demonstrations [12][13][14][15][16].…”
supporting
confidence: 50%
See 1 more Smart Citation
“…In addition, the highest CE of only −0.58 dB with 3 dB bandwidth of 71 nm was obtained at a coupling angle of 13°. The back reflection of the grating coupler was extracted from the contrast of the Fabry-Perot (FP) fringes of the fiber-to-fiber transmission spectrum, and is lower than 1.4% at the peak coupling wavelength, which is comparable to previous demonstrations [12][13][14][15][16].…”
supporting
confidence: 50%
“…Moreover, the CE of such uniform shallowly etched grating couplers is limited not only by power leakage to the substrate, but also by the intrinsic mode mismatch between the gratings and SSMFs. For applications where only fully etched silicon waveguides are present on a photonic-integrated circuit, such as multimode multiplexers [9] or multicore fiber couplers [10], fully etched grating couplers are preferred [11][12][13][14][15][16] in order to simplify the fabrication process. Table 1 summarizes the performances of state-of-theart fully etched and shallowly etched grating couplers that have been demonstrated over the past few years.…”
mentioning
confidence: 99%
“…Since the first experimental demonstration of an optical waveguide with a subwavelength periodic core [4], these structures, also called subwavelength gratings (SWGs), have found many applications in integrated optics, for example as highly efficient fiber-chip couplers [3][4][5][6][7][8][9], low-loss waveguide crossings, evanescent field sensors [10,11], broadband directional couplers [12] and multimode interference (MMI) [13] couplers, polarization beam splitters [14][15][16], wavelength division [4] and mode division [17] multiplexers, delay lines [18], Fourier-transform spectrometers [19] and suspended (membrane) waveguides for mid-infrared applications [20]. Exhaustive reviews of SWG fundamentals and applications can be found in [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, different from the slot PCW modulator in Section III, multimode interference (MMI) couplers are used for beam splitting and combining [73], a through-etched subwavelength grating (SWG) with over 50% efficiency are designed to couple light into and out of the silicon strip [74].…”
Section: A Designmentioning
confidence: 99%